Mechanical properties of caco3 extracted from cockle shell with high density polyethylene (HDPE) for biomaterials in bone substitute application - Yusup, E.; Roslan, A. R.; Siswanto, W.A.; Ngali, Zamani; Salleh, S.; Mohamad, Z.; Wan Daud, W. R.; Roslan, R. (SINTE, 2018)
This study was conducted to produce CaCO3 powder extracted from cockle shells as bioceramic materials which later combined with high density polyethylene (HDPE) as the polymer to produce composite as the final product. For CaCO3 clarification, the powder form of bioceramics was analyzed using FTIR, SEM and EDX analyses. Then, the composites produced were tested for mechanical properties via tensile and hardness tests. Firstly, the wasted cockle shells were all washed to remove dirts and soaked in regular water overnight before left to dry at room temperature. Then, they were all ground up between range 100 – 200 µm several times until the required size were obtained. The spectrum for FTIR showed identical result as previous work at reading 857.22cm-1 which represent vibrational bonds that can be attributed to the characteristics of external plane bending vibration of carbonate. After the confirmation, it was added to the melted HDPE to produce stronger composite via injection moulding method. Injection moulding process was to produce the sample into the shape of dumbbell to perform mechanical tests, tensile and hardness test with three parameters for each weight ratio. It could be concluded that pressure, velocity and temperature affecting the hardness of samples. In this research, the greatest value of Young’s modulus and maximum force which are 852.2 MPa and 271.457 kN, respectively. In conclusion, cockle shell could become great biomaterial as it provide good in mechanical properties. Furthermore, the source also abundantly available and with the fully usage of this waste to something more useful, it is able to reduce contamination to the earth. Then, the combination with any polymer is able to produce strong composite that could apply in any field. For this research, the composite is focus in biomaterial usage, especially in orthopaedic field for bone implant. For instance, CaCO3 are proved to be function at higher temperature, and further future works might be required to search the maximum temperature that this material could achieve.